Síntese e caracterização de nanocristais ternários de MgCdS e nanocompósito de MgCdS e derivados de grafeno - Souza Junior, Helio Oliveira (2017)
In this work the synthesis of MgCdS ternary semiconductor nanocrystal alloys has been carried out by aqueous route through a bottom-up approach, using conventional hydrothermal heating as well as in situ onto graphene matrices. In the synthesis of MgCdS nanocrystals, the effect of each reaction parameter on the spectroscopic properties was studied aiming to understand the possibilities to control the optical properties. Emission spectra of MgCdS samples obtained in the experiments designed to optimize reaction parameters exhibited a single emission band reflecting nanocrystal growth, with quantum yields as high as 85%. Based on the presence of two bands in absorption spectra as well as atomic absorption spectrometry (AAS) data it was possible to propose that nanocrystals are composed of Cd and Mg. Concerning the structural architecture, it has been proposed that nanocrystals show a core-shell structure with a diffuse interface. Data from AAS also showed that the final composition of nanocrystals is generally different from the initial reaction Cd:Mg proportion, as the metal precursors have distinct reactivities. Morphological analyses by transmission electron microscopy (TEM) of nanocrystals evidenced the predominance of spherical shapes and sizes below 4 nm. Studies of the formation of nanocrystal alloys with Mg1-xCdxS and Cd1-xMgxS composition, by ion exchange from the binary components MgS and CdS helped the discussion of spectroscopic behavior of the ternary system MgCdS. It was possible to confirm that the introduction of a second cation (Cd2+ or Mg2+) into each binary structure (MgS or CdS) is consistent with the observation of two absorption bands and only one emission band. The addition of graphene derivatives during the synthesis of MgCdS nanocrystals was carried out aiming to improve the properties of the materials, as well as providing a physical support to the nanocrystals, favoring future applications. The presence of graphene induced shifts in the emission bands to larger wavelengths concomitant with intensity reduction, which can be taken as evidence of interactions between the materials. The morphologies of composites were characterized by typical graphene sheets decorated with spherical nanocrystals.